Development of Liping Arts Methods (Performance, Exploration, Brainstorming) in PKN Learning - Budiwan, Jauhan; Sholihah, Abdah Munfaridatus (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
One interesting learning method is the Liping Arts. This method is used in lessons with many stories or events that students must memorize. The Attribute Dimension is a set of equipment used by students in practicing lessons with the Story Liping Arts method. This study aims to test the effectiveness of the story lip art method assisted by attribute dimensions developed with a performance, exploration, and brainstorming approach in civics learning at SDN Patihan Wetan Ponorogo Indonesia. The research method used in this research is descriptive qualitative. Sources of data were obtained from observation, pre-test, and post-test. The results of this study are the Story Liping Arts method assisted by Attribute Dimensions, which was developed using the PEB approach. The syntax of the PEB approach was obtained from an analysis of the Scientific Approach to the MBKM Curriculum and 21st Century Learning Skills. Applying to learning with the Story Liping Arts method assisted by Attribute Dimensions has proven effective and beneficial for students' knowledge and experience because the essence of effective learning is to experience it in real time.